Val1483Ile in FASN Gene Is Linked to Central Obesity and Insulin Sensitivity in Adult White Men - Moreno‐Navarrete, José M.; Botas, Patricia; Valdés, Sergio; Ortega, Francisco J.; Delgado, Elías; Vázquez‐Martín, Alejandro; Bassols, Judit; Pardo, Gerard; Ricart, Wifredo; Menéndez, Javier A.; Fernández‐Real, José M. (Obesity (Silver Spring, Md.), 2009)
The Val1483Ile polymorphism in the human fatty acid synthase (FASN) gene is located within the interdomain region of the FASN close to the two dynamic active centers of the FASN enzyme and putatively affects FASN action. We aimed to evaluate the association of this polymorphism with obesity phenotypes, insulin sensitivity, and adipose tissue FASN activity in adult white subjects. The polymorphism was evaluated in association with metabolic variables in two independent studies: in a case–control study of 457 men (229 with normal glucose tolerance (NGT) and 228 with altered glucose tolerance (AGT)); and in 600 population‐based NGT subjects (274 men and 326 women). Adipose tissue FASN activity was analyzed using the method of Nepokroeff. The Ile variant was associated with a lower waist‐to‐hip ratio (WHR) and a lower increase in weight over a 7‐year period in NGT men. In a subset of 147 men, carriers of the Ile variant showed significantly increased insulin sensitivity. BMI (P < 0.001), WHR (P = 0.03), and Val1483Ile (P = 0.03), contributed independently to 37% of insulin sensitivity variance. In men from the population‐based study, the Ile variant was associated with a lower BMI, WHR, fasting glucose, and systolic blood pressure compared with carriers of the Val variant. In agreement with these results, the adipose tissue FASN activity was significantly lower in subjects with the Ile variant (P = 0.01). In summary, adult white men with the Ile 1483 variant of the FASN gene seem protected from developing central obesity through decreased adipose tissue FASN activity.